Performance Improvement by Mitigating the Effects of Moving Cloud Conditions - Tatabhatla, Venkata Madhava Ram; Agarwal, Anshul; Kanumuri, Tirupathiraju (IEEE transactions on power electronics, 2021)
Partial shading is an important subject for the research community to improve the issues in the field of solar array utilization. Shading decreases the life of photovoltaic array, its output power yield, and also generates several peaks in its P - V characteristic curves. Physical relocation of panels can be used as a practical solution to prevent such problems by altering the location of panels but not its electrical circuit. In this article, a reconfiguration technique for all conventional configurations like, series-parallel, bridge-link, honey comb, and total cross tied connections are proposed to reduce current difference between the rows and to improve the irradiance equalization by dispersing the shade. This article proposes a mathematical Tom-Tom puzzle pattern for 5× 5 array to enhance the output parameters. The performance of all configurations is evaluated with artificially generated shading to resemble moving clouds which are incremented progressively in row-wise and diagonal manner. From the extensive analysis of results, it has been found that the proposed reconfigurations show better performance than its respective static configurations. The proposed configuration is also tested in terms of income generated and a comparison with the existing state-of-art methods to show the supremacy of the proposed approach.